Trends in Single‐Use Mixing for Biomanufacturing with an Insight Into Lonza Ibex® Solutions. Issue 12 (9th November 2022) - de Boulard, Arnaud; Kienle, Klaus
Abstract: Biologics manufacturing has seen many new developments in recent years. The industry is moving away from processing systems based on stainless steel (with cleaning and validation requirements) to single‐use systems (sterilized, disposable plastics). This communication presents an overview of the current single‐use mixing technology landscape, requirements and challenges driven by the need for versatile biomanufacturing platforms with increased productivity. A case study is presented with an insight into Lonza Ibex® Solutions. Abstract : This article presents general utilization of single‐use mixing in biotechnology processes. It starts with an understanding of markets trends fostering single use, goes through a snapshot of Lonza Ibex Solutions, describes the mixing challenges for the main bioprocess steps, and introduces the single‐use mixing technology landscape.